Hubungan Kondisi Lingkungan Fisik dan Tindakan PSN Masyarakat Dengan Container Index Jentik Ae. aegypti di Wilayah Buffer Bandara Temindung Samarinda - Anwar, Andi; Rahmat, Ade (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
The high dengue cases in Indonesia is very closely linked to environmental conditions. There are still many people who do not understand the environmental conditions that can lead to the spread of dengue disease. Environmental conditions are conditions that could affect the development of larvae of Aedes aegypti. Breeding and resting places of dengue vectors such as containers contain-ing water, humidity, lighting and air temperature can be a big threat for the spread of dengue dis-ease. In addition to the environmental conditions, actions / practices mosquito nest eradication (PSN) community is still very necessary in the note to prevent dengue disease. The working area Temindung dengue cases in the Village of service in 2012 there were 5 cases of dengue fever patients, and in-creased cases in the year 2013 as many as 6 cases. This study aims to determine the relationship Knowing the physical environment and the actions PSN community with Container Index (CI) Aedes aegypti in the buffer area Temindung Samarinda in 2014. This type of research is analytic survey method with cross sectional approach. Samples are 112 respondents by observation, observation and measurement. The results showed no relationship between the humidity of the Container Index with sig value of 0.001 (sig> α), there is a relationship between the lighting of the Container Index with sig value of 0.001 (sig <α), There is a relationship between air temperature of the Container Index with sig 0,001 (sig <α), and there is a relationship between the PSN to the Container Index (CI) with a value of 0.001 ρ (ρ value <α). Based on the results of this study are expected to provide input into PSN and abatisasi program so as to minimize the Flick Ae. aegypti in the region Buffer Temindung Samarinda. Keywords : Container Index, Physical Environment, PSN